The Realization of Metaphor Types in Green’s The Fault inOur Stars (2012) - Ayu Dewi Fatimah; Hendi Pratama; Dwi Rukmini (Universitas Negeri Semarang, 2022)
Metaphors deal with transferring words to other words by comparing the similarity of its meaning. This study investigated the realization of metaphors and their relationship among the four types in the novel. Lakoff and Johnson; Lakoff and Turner mentioned four metaphors; those are structural metaphors, orientational metaphors, ontological metaphors, and image metaphors. These metaphor categorizations are mentioned in the Contemporary Theory of Metaphors (CTM). The researchers conducted a linguistic analysis of text as the method. To collect the data, the researchers used MIPVU (Metaphor Identification Procedure Vrije Universiteit) in The Fault in Our Stars by John Green. The metaphors which are found were analyzed based on classifications as they are used in the novel. In this study, there are 367 metaphors found in the novel; those are 56 structural metaphors, 40 orientational metaphors, 222 ontological metaphors, 36 image metaphors, and 13 compound metaphors. The most used metaphor in the novel is Ontological metaphor because it has more general specification than other metaphors. The compound metaphors are found based on the relationship of the four types. They are used together to strengthen, clarify, support, complete, and continue each other. The results presented that all of the metaphors are mapped in a proper way. It means they have compatible concepts transferred. Thus, this result can be used by the learners as supporting words to raise the learners' quality of speech.